Effect Of Pulsed Electromagnetic Field Therapy Combined With A Tailored Exercise Program In Patients With Chemotherapy-Induced Neuropathy Following Breast Cancer Treatment (The Review of Diabetic Studies, 2025)
Background: Chemotherapy-induced neuropathy (CIPN) is a common complication in breast cancer (BC), often resulting in pain, balance issues, and functional decline. Addressing these symptoms is vital for improving quality of life and recovery. Purpose: This study evaluated the effectiveness of combining pulsed electromagnetic field (PEMF) therapy with a tailored exercise program (TEP) in managing CIPN symptoms, specifically targeting pain, balance, and functional recovery. Method: A randomized controlled trial was carried out on Eighty patients with breast cancer were randomly assigned to an study group (PEMF + TEP) or a control group (TEP alone). Intervention was conducted for eight weeks. Pain intensity was measured using the Visual Analog Scale (VAS), functional status via the Functional Assessment of Cancer Therapy–Neurotoxicity (FACT-Ntx), balance through the Berg Balance Scale (BBS), and nerve conduction velocity (NCV) tests. Results: The Study Group demonstrated a significantly greater reduction in pain (VAS mean decrease: 6.20 vs. 4.20; p < 0.0001). Both groups showed significant functional improvements (FACT-Ntx mean difference = 10.30; p < 0.001). Balance improved more in the Study Group, with mean differences of 5.80 in sway and 1.93 in stability indices. NCV results further supported improved nerve function in the Study Group.Conclusion: Combining PEMF therapy with a tailored exercise program significantly reduced pain, enhanced functional status, improved balance, and positively influenced nerve conduction in patients with breast cancer experiencing CIPN. These findings support integrated therapeutic approaches as effective strategies for managing chemotherapy-induced symptoms and improving patient outcomes and quality of life.